Synthesis and Characterization of Diesel Lubricity Enhancer through Transesterification Reaction of Palm Oil with 1,2-Ethanediol - Yulfi Zetra; Sovia Masfuri Walidatus Sholihah; R. Y. Perry Burhan; R. Arizal Firmansyah (Universitas Muhammadiyah Magelang, 2021)
Desulphurization of diesel fuel is necessary to be done to reduce sulphur content in the air. However, the desulphurization process will reduce the lubrication properties of diesel fuel. In order to overcome the problem, it needs bioadditive to improve the lubricity. Lubricity of diesel fuel can be improved by the subsistence of chemical compound that is hydroxyethyl esther (HEE). HEE is synthesized through the transesterification reaction of palm oil (triglycerides) and 1,2 ethanediol at 150 Â°C for 5 hours and K2CO3 catalyst as well. The conversion of TG into the products is 72.90%. The characterization using Gas Chromatography-Mass Spectrometry (GC-MS) indicates that the chemical compound in synthesis products comprise free fatty acids, hydroxyethyl esters and by-products. The obtained products can be used as bioadditives to improve the lubricity of diesel fuel.